Biotech and Justice: Catching up with the Real World Order - Cahill, Lisa Sowle (The Hastings Center report, 2003)
Social policy questions in the U.S. are often framed in terms of individual rights, valorizing individual freedom and self-determination. But this focus obscures the social and economic bases of health and disease. U.S. bioethics, as its counterparts in Africa and Asia have done, needs to restructure its philosophical framework and expand its moral criteria to consider how to define a global ethics.